Voxel-wise lesion mapping of restless legs syndrome in multiple sclerosis - Fröhlich, Kilian; Knott, Michael; Hock, Stefan; Dörfler, Arnd; Seifert, Frank; Winder, Klemens (Neurological Sciences, 2022)
Objective Restless legs syndrome (RLS) is known to be associated with multiple sclerosis (MS) and may be caused by MS lesions in specific cerebral brain regions. Applying a voxel-wise lesion analysis, we tried to identify the contribution of cerebral MS lesions to RLS. Methods In this retrospective study, we established a cohort of people with MS with documented RLS and controls of people with MS without RLS matched disease severity. Diagnosis of MS and RLS was based on the current guidelines. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T). After manual delineation, lesion maps were converted into stereotaxic space. We generated a lesion overlap and performed a Liebermeister test with 4000 permutations to compare the absence or presence of RLS voxel-wise between patients with and without lesions in a given voxel. Results Forty of the patients with RLS and MS fulfilled the inclusion criteria. The voxel-wise analysis yielded associations between RLS and MS in the subcortex of the left gyrus precentralis. Conclusion Our voxel-wise analysis shows associations in the subcortex of the left gyrus precentralis. Thus, our data suggests that a dysfunction of the efferent motor system due to cerebral lesions may contribute to the pathophysiology of RLS in MS.
CRIS-Team WoS Importer:2022-05-20